The Study of the Landscape Restoration and Reuse of Foreign Company Facilities in Tamsui, Taiwan - Chang, Chih-Yuan (International Journal of Natural Sciences Research, 2018)
This paper discusses both the surviving and now-disappeared foreign company facilities in Tamsui. The discussion topics include historical analysis of foreign firms and suggestions for preservation and reconstruction. The methodology of this study combines historical research of architecture with discussion of the cultural landscape, and proposes a discussion of lost landscapes and the preservation of the existing foreign company facilities in Tamsui. The Shell Company and the Douglas Lapraik & Co. warehouses in Tamsui are the witness and the cases of well-preserved with a scarcity value. These cases warrant preservation as a heritage site based on their historical value and for reasons of environmental sustainability. A representation of the foreign company storage and sites should be displayed in the Tamsui eco-museum for inclusion with the other historical heritage areas in Tamsui.